Posterior cruciate ligament injury: characteristics and associations of most frequent injuries - Marco Tulio Lopes Caldas; Gilberto Ferreira Braga; Samuel Lopes Mendes; Juliano Martins da Silveira; Robson Massi Kopke (Revista Brasileira de Ortopedia, 2013)
OBJECTIVE: To investigate the prevalence and combinations of PCL injuries and their correlations with the mechanism, the occurrence of evident dislocation and associated fracture. METHOD: A retrospective study of 85 lesions of PCL operated between 2003 and 2010. Diagnosis by physical examination and dynamic radiography, compared with surgical findings. RESULTS: Injuries involving the PCL were more prevalent in men (78.8%) with a mean age of 33 years. The main cause was traffic accidents (73.80%), and (49.4%) motorcycle. Isolated PCL injury occurred in (15.3%) cases, and combined (84.7%). Among the isolated lesions, bone avulsions were nine (10.6%). The most associated PCL injuries were the ACL (48.2%), followed by LCL PCL/PLC (22.4%). Fractures were more associated with combining PCL + LCL/PLC injuries and did not appear in the PCL + MCL/PMC. Complications beyond fractures: peripheral nerve injury (4.8%) and vascular (1.2%). Evident dislocation in primary care (16.7%) was more prevalent in combined ACL + PCL + MCL/PMC (44.4%). Half the patients were operated during the acute phase. There was a statistically significant difference (p < 0.05) comparing each combination of ligament injuries with the presence of fracture, dislocation or clear mechanism of injury. CONCLUSION: Surgical treatment of PCL injuries in a center for orthopedic trauma care was mostly multiligament and mainly involving the ACL. A significant association was seen between the type of injury with mechanism of injury, presentation of the knee, if dislocated or reduced, and the presence of associated fracture.